Basis of monetary policy and its goals and objectives in the Islamic economy - بكر, شەوبۆ عثمان; الكريم, ياسين صالح عبد (Sulaimani Journal for Humanities, 2019)
It is well known that economy is one of the most important sciences of nowadays because of the important role it plays in all the aspects of human life . It has number one influence on all the social, political, militarian aspects And surely the most important part of economy is currency and policies related to it. Because money is the reason behind the trade and the unite measure of the agreements that is why currency and it’s stability and the level of business men’s trust in the stocks defines the economy of every country And that’s why a country’s economy has downs and even failures. That’s why Economical policy has been one of the top topics of economical science in globe. In the shadow of this I have done this research about currency policies in Islamic economy so that we can clarify Islamic economy is perfectly oriented and it can suit every situations it is a good replacement for every solutions and it has best answer to every question.